Prevention of unwanted pregnancy in adolescents - Fatchurrahmi, Rifka; Sholichah, Mutingatu (Universitas Muhammadiyah Magelang, 2021)
Adolescence is a transitional period between children and adults, where there is rapid growth, secondary sex characteristics arise, fertilization is achieved and psychological and cognitive changes occur. However, the level of adolescent knowledge about reproductive health is still low. As a result of the lack of knowledge of adolescents about reproductive health, among others, the increase in the number of unwanted pregnancy. Unwanted pregnancy in adolescents also occurs in one area in Yogyakarta city, so that community-based preventive interventions are needed. The intervention provided was in the form of psychoeducational activities for adolescents and parents. Parents are given intervention because they have a role in preventing unwanted pregnancies in adolescents, for example by maintaining effective communication with adolescents and getting used to being open mind. The results of this activity have proven to be effective because they can increase knowledge significantly.